Fearsome Ñapaq? - Manya, Juan Antonio (1969)
In the history of the peoples, there are certain beliefs, which have been dragged on since the time of the Incas, as a legendary tradition, which in most cases are fictitious, which attribute extraordinary physical, intellectual and technical qualities to beings created by the imagination. Thus, the "Ñak'aq", the damned, aukis, devil, sirens, etc., are themes that certain people have been able to take advantage of and give them color according to the circumstances, although they constantly undergo modifications, sometimes mutilations. and other additions to the original narrative.